A comparison of surface and total deltamethrin levels of insecticide-treated nets and estimation of the effective insecticidal lifetime - Green, M; Maxyay, M; Pongvongsa, T; Phompida, S; Swamidoss, I; Smith, S; Irish, S; Newton, P (American Society of Tropical Medicine and Hygiene, 2021)
The ability to anticipate the useful lifetime of an insecticide-treated mosquito net (ITN) would provide a proactive approach for planning net distribution programs. Therefore, we used an exponential decay model of deltamethrin depletion to predict the effective insecticidal lifetime of PermaNet® 2.0 nets used in the Lao PDR. Residual deltamethrin was measured using two nondestructive analytical field methods; X-ray fluorescence (total levels) and a colorimetric field test (surface levels) at 12 and 24 months postdistribution. The model assumes that the 12-month depletion rate can be used to predict future levels. The median total and surface deltamethrin levels for the Lao nets at 12 months were 31.2 and 0.0743 mg/m2, respectively. By defining a failed net as having total deltamethrin levels of less than 15 mg/m2 or a surface level less than 0.0028 mg/m2, it was predicted that 50% of the group of nets will fail at about 27 months after distribution.